Synchronous Gastric Gastrointestinal Stromal Tumor and Colon Adenocarcinoma: A Case Report - Thivi Vasilakaki; Kalliroi Koulia; Aikaterini Tsavari; Elissavet Arkoumani; Efstratios Kouroumpas; Anargiros Pavlis; Georgios Christopoulos; Konstantinos Stamatiou; Kassiani Manoloudaki; Dimitrios Zisis (Case Reports in Oncological Medicine)
Gastrointestinal stromal tumors (GISTs) represent the majority of primary mesenchymal tumors of the gastrointestinal tract. They are generally considered to be solitary tumors and therefore the synchronous occurrence with other primary malignancies of gastrointestinal track is considered a rare event. Here we present the case of a 75-year-old man admitted to our hospital with a 10-day history of gastrointestinal bleeding. Colonoscopy revealed an ulcerative mass of 4 cm in diameter in the ascending colon. Gastroscopy revealed a bulge in the gastric body measuring 1 cm in diameter with normal overlying mucosa. Surgical intervention was suggested and ileohemicolectomy with regional lymph node resection along with gastric wedge resection was performed. Pathologic examination of the ascending colon mass showed an invasive moderately differentiated adenocarcinoma stage III B (T3N1M0). Grossly resected wedge of stomach showed a well circumscribed intramural tumor which microscopically was consistent with essentially benign gastrointestinal stromal tumor (according to Miettinen criteria). The patient did not receive additional treatment. Two years later the patient showed no evidence of recurrence or metastasis.